Application of 3D technology for modelling of architectural monuments in the Czech repub - Vach, K. (КНУБА, 2018)
The paper is devoted to consideration the questions of 3D technology application for modelling of architectural monuments in the Czech Republic. 3D in case of conservation of historical and cultural monuments means the processing of measured data with the required contents in the local system of coordinates and in a chosen scale. According the results obtained it is necessary to determine the requirements for measuring accuracy. The main goal of our research is early detection of errors in 3D images of actual building behavior and their exception, as well as introduction of new technologies into existing processes and implementation of new technologies into GIS. The methodology for documenting the actual object behavior in 3D is defined and outlined in the paper. As an example of a system for documentation and monitoring of cultural heritage objects, the paper considers a database created in the Czech Republic
Застосування технології тривимірного моделювання для моделювання пам'ятників архітектури в Чеській республіці
Применение технологии трехмерного моделирования для моделирования памятников архитектуры в Чешской республике
Keywords: accuracy; details in documenting the architectural monuments; methodology; actual object behavior in 3D; photogrammetric survey; 72(437.3):519.876